Measurement and processing of fast pulsed discharge current in plasma focus machines - Lee, S.; Saw, S. H.; Rawat, R. S.; Lee, P.; Verma, R.; Talebitaher, A.; Hassan, S. M.; Abdou, A. E; Mohamed, Ismail; Mohamed, Amgad; Torreblanca, H.; Al Hawat, Sh.; et al. (Springer US, 2012)
The fast pulsed electric discharge current drives all physical processes in the plasma focus device; in turn all physical processes in the focus affect the current waveform. Thus the discharge current waveform is the most important indicator of plasma focus performance. This underlies the importance of properly measuring, processing and interpreting the discharge current waveform. This paper reports the measurement of fast pulsed discharge current by the Rogowski coil, in two different modes: the current transformer, “I” mode, and current derivative, “Idot” mode. The processing and interpretation of recorded current waveform to obtain useful information about the physical processes in the plasma focus device are discussed. The current transformer with a large number of turns and a sub-1 Ohm terminator has good high frequency response, necessary for the sharp current dip region when dI/dt exceeds 2 × 1011 A/s. However the signal is “noisy” in the current dip region. Several methods to extract the current dip from the noise are discussed and examples of how low pass filters affect the signals are shown. The dI/dt coil, the Rogowski coil in “Idot” mode, with a few turns terminated by 50-Ohm is also described. Integrating the 1 GSa/s digital waveform does remove the high frequency noise components, yet the extracted waveform shows sharp angular features indicative of the retention of short-time features. This makes the dI/dt coil superior to the current transformer. A 7-turn coil is tested against the Lee Model code and found to be suitable to measure the plasma focus discharge current.